Professional training for primary school teachers on the basis of the task-based approach - Oleksenko, Karina; Kryvylova, Olena; Sosnickaya, Natalya; Molodychenko, Valentin; Kushnirova, Tetiana (Linguistics and Culture Review, 2021)
The aim of the article is the theoretical justification of the task-based approach as a methodological basis for the formation of future elementary school teachers’ readiness to design the learning environment. The research methodology includes the analysis of regulatory documents, psychological and pedagogical literature and scientific research to determine the essence of the task-based approach and its implementation features in the formation of future elementary school teachers’ readiness to design the learning environment. Distinguishing between the stages of preparing future elementary school teachers for designing learning environments and their purpose influenced the development of a specialized task system and practical problems which can be divided into three groups: adaptive, stabilizing, specialized. When selecting and developing specialized tasks and practical problems have been acted according to the following algorithm: assignment of a task or practical problem (adaptation, stabilization, specialization) determination of expected results in accordance with the components of readiness and the predominant choice; evaluation of the content complexity on the B. Bloom’s scale.